PERANAN SENI MUSIK DALAM IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DI SMP XAVERIUS BUKITTINGGI - Husnil Insani; Nurul Fadhilah Siregar; Khairunnisa Adriani; Mulyadi; Ade Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe and analyze the role of musical arts in the implementation of multicultural education at Xaverius Middle School, Bukittinggi. The background of the study stems from the urgency of multicultural education as a strategy to reduce the potential for conflict arising from cultural and religious diversity, and students social backgrounds. Multicultural education is considered important because it can foster mutual respect and tolerance in a diverse school environment. The research method uses a descriptive qualitative approach with data collection techniques through interviews and observations. Data analysis is carried out through the processes of reduction, presentation, drawing conclusions and verification. The results of the study indicate that musical arts have a significant contribution in instilling multicultural values, such as tolerance, togetherness, and respect for differences. Implementation is carried out through intracurricular and extracurricular activities involving students from diverse backgrounds, thus creating an inclusive, harmonious learning atmosphere and supporting positive interactions between students. Obstacles faced include limited time, differences in interests, and variations in student abilities, but these do not reduce the achievement of the overall research objectives.